Review on green data center frameworks - Mohd Nor, Norhashimi; Selamat, Mohd Hasan (IEEE (IEEE Xplore), 2014)
Data centers are the heart of computing and emergence of internet services demands has increased its vitality. The intense workload of data centers in order to fulfill customers need indirectly contributed to world pollution through massive usage of energy. Thus an energy efficient framework for steering the data centers design and management is needed. Besides the green factor, the framework should take into consideration total cost of ownership (TCO) as one of the key components to make it budget friendly and feasible to all kind of budget. To achieve this, comparison on five existing energy efficient data center framework was performed. The comparison deduced that the frameworks have the opportunities for improvement in term of components, attributes, energy efficient metrics and implementation methodology. Propositions and novel ideas from industry leaders are also gathered to provide diverse views on energy efficiency approaches and opportunities in data center. Categorization of attributes based on return on investment (ROI) and energy efficiency level in one of the frameworks that allows it to be implemented in phases is a sensible and practical approach. Works focusing on developing higher ROI attributes will definitely contribute in building more energy efficient and greener data center in the future.